Study on monomer functional suitability toward sofosbuvir in molecularly imprinted polymer: In silico and experimental study - Hilda Aprilia Wisnuwardhani; Slamet Ibrahim; Rino Rakhmata Mukti; Sophi Damayanti (Composites Part C: Open Access, 2023)
Sofosbuvir (SOF) is an anti-HCV (Hepatitis C Virus) used as an off-label drug in treating COVID-19 and the usage requires good therapeutic drug monitoring, with analytical and suitable sample preparation methods. Therefore, this research aimed to apply in silico and laboratory testing in preparing SOF molecularly imprinted polymers (MIP). MIP is expected to improve sample preparation performance. The best functional monomer and porogen selection were determined through the use of Density Functional Theory (DFT) method with the B3LYP basis set 6–31G (d,p) and molecular dynamics simulation. The association constant test and Jobs plot were determined by the UV spectrophotometry and MIP synthesis method was conducted by bulk and precipitation polymerization. The polymer particles underwent characterization using Fourier-transform infrared spectroscopy and scanning electron microscopy. The result showed that methacrylic acid (MAA) and acetonitrile were the best functional monomer and porogen for synthesis. Precipitation polymerization yielded superior outcomes in terms of polymer homogeneity and adsorption capability compared to bulk polymerization. Polymer, MIP B, with a composition ratio of template:functional monomer:cross-linkers = 1:1:20, which was synthesized by the precipitation method, provided the best adsorption capability in all solvents tested, and had an imprinting factor of 1.15.